Stories of immoral and harassed teachers: gender, education and discipline in the school system of Argentina (1919-1935) - Cammarota, Adrian (Historia y Memoria de la Educación, 2020)
The purpose of this paper is to analyze the relationship between gender and education by taking as a reference the case of three teachers who were punished for assumed moral offences committed in their private sphere. Two of these teachers were exonerated. These events took place in 1919, 1921 and 1935 in Mendoza, Chubut and Rio Negro provinces, respectively. Furthermore, we will carry out the analysis of a file on an alleged harassment committed by senior male staff members. Morality was one of the pillars sustained in academic teacher training and served as a method of controlling the teaching staff. In many respects, this search deals with the disciplinary mechanisms applied by the Consejo Nacional de Educación (National Board of Education, CNE), which strove to regulate bodies and behavior in response to the assumed immoralities committed by the teaching staff. We develop a descriptive analysis as a way of delving into representations, mindsets and patriarchal mandates reproduced in the school system.